3D-Printed Poly(lactic acid)/Poly(ethylene glycol) Scaffolds with Shape-Memory Effect near Physiological Temperature; Polymers; Vol. 18, iss. 1 - Fetisova A. A. Anastasiya Alekseevna; Abdullah bin F. Firoz; Lozhkomoev A. S. Aleksandr Sergeevich; Senkina E. I. Elena Ivanovna; Ryumin E. E. Egor Evgenjevich; Surmeneva M. A. Maria Alexandrovna; Surmenev R. A. Roman Anatolievich (2026, 2026)
Title screen